The immunoregulatory abilities of polymorphonuclear neutrophils in the course of multiple sclerosis. - Ziaber, J (1998)
The polymorphonuclear neutrophils (PMN) possess sufficient potential to affect both immune response and inflammation, however it has not been yet described in the course of multiple sclerosis (MS). We have studied binding of fluorescein isothiocyanate (FITC)- stained TNF-alpha by PMN, the expression of CD11a, CD11b, and CD18 molecules of beta2-integrines and the expression of CD10 (neutral endopeptidase-NEP) and of CD13 (aminopeptidase N; APN) antigens on PMN in three different groups of MS patients. The control group included neurological patients (OND) with noninflammatory diseases. The obtained results have proved that during MS exacerbation and in the course of chronic progressive MS, PMN reveal several forms of preactivation, including significantly higher stained-TNF-alpha binding, higher expression of CD11b and CD18, as well as CD10 and CD13 antigens, in comparison with MS remission or OND. We suggest that the increased expression of these molecules on PMN of MS patients in exacerbation of the disease and to a lower degree in the course of CP-MS is a result of PMN priming, and directly prove the PMN involvement in the disease pathogenesis.